Tapentadol versus oxycodone analgesia and side effects after laparoscopic hysterectomy: A randomised controlled trial. Issue 9 (September 2021) - Comelon, Marlin; Raeder, Johan; Drægni, Tomas; Lieng, Marit; Lenz, Harald
Abstract : BACKGROUND: Tapentadol is an opioid, which acts as a μ-opioid receptor agonist and inhibits noradrenaline reuptake in the central nervous system. This dual mechanism of action results in synergistic analgesic effects and potentially less side effects. This has been shown in treatment of chronic pain but postoperative studies are sparse. OBJECTIVES: The main aim was to compare the analgesic effect of tapentadol with oxycodone after laparoscopic hysterectomy. Opioid side effects were recorded as secondary outcomes. DESIGN: Randomised, blinded trial. SETTING: Single-centre, Oslo University Hospital, Norway, December 2017 to February 2019. PATIENTS: Eighty-six opioid-naïve American Society of Anesthesiologists physical status 1 to 3 women undergoing laparoscopic hysterectomy for nonmalignant conditions. INTERVENTION: The patients received either oral tapentadol (group T) or oxycodone (group O) as part of multimodal pain treatment. Extended-release study medicine was administered 1 h preoperatively and after 12 h. Immediate-release study medicine was used as rescue analgesia. MAIN OUTCOME MEASURES: Pain scores, opioid consumption and opioid-induced side effects were evaluated during the first 24 h after surgery. RESULTS: The groups scored similarly for pain at rest using a numerical rating scale (NRS) 1 h postoperatively (group T 4.4, 95% CI, 3.8 to 5.0, group O 4.6, 95% CI, 3.8 to 5.3). No statistically significant differences were found between the groups for NRS at rest or while coughing during the 24-h follow-up period ( P = 0.857 and P = 0.973). Mean dose of oral rescue medicine was similar for the groups ( P = 0.914). Group T had significantly lower odds for nausea at 2 and 3 h postoperatively ( P = 0.040, P = 0.020) and less need for antiemetics than group O. No differences were found for respiratory depression, vomiting, dizziness, pruritus, headache or sedation. CONCLUSION: We found tapentadol to be similar in analgesic efficacy to oxycodone during the first 24 h after hysterectomy, but with significantly less nausea. TRIAL REGISTRATION: ClinicalTrials.gov, NCT03314792.